2015
DOI: 10.1039/c5ra03423j
|View full text |Cite
|
Sign up to set email alerts
|

Novel multi-sensitive pseudo-poly(amino acid) for effective intracellular drug delivery

Abstract: A novel intracellular pH, glutathione (GSH) and reactive oxygen species (ROS)-responsive nanoparticles were obtained using mPEG 2k -block-redox dual sensitive chain-block-mPEG 2k (PRDSP) which was prepared by Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC) Click polymerization. The disulfide bond, peroxalate ester and triazole units were regularly and repeatedly arranged in the hydrophobic 10 blocks. The disulfide bond was GSH-sensitive and peroxalate ester structure could be disrupted by acid and hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…B) Preparation of DOX‐loaded PRDSP nanoparticles, their uptake and intracellular microenvironment triggered release of DOX. Reproduced with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Ros‐triggered Drug Release From Polymeric Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…B) Preparation of DOX‐loaded PRDSP nanoparticles, their uptake and intracellular microenvironment triggered release of DOX. Reproduced with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Ros‐triggered Drug Release From Polymeric Nanoparticlesmentioning
confidence: 99%
“…To increase the sensitivity of the peroxalate‐based nanoparticles, Wu et al synthesized a dual sensitive ABA‐type amphiphilic triblock polymer (PRDSP), wherein the middle hydrophobic block was incorporated with peroxalate ester units and disulfide bonds repeatedly, and PEGs were selected as outer hydrophilic blocks . The DOX‐loaded PRDSP nanoparticles showed accelerated release of DOX under biologically relevant concentration of glutathione (10 m m ) and H 2 O 2 (10 m m ) compared to the physiological conditions (Figure B).…”
Section: Ros‐triggered Drug Release From Polymeric Nanoparticlesmentioning
confidence: 99%
“…Kang and co‐workers developed H 2 O 2 reactive hydroxybenzyl alcohol‐based nanoparticles to effectively release fluorescent probes and drugs toward the application of imaging and therapy of ischemia‐reperfusion injury. More recently, Huang and co‐workers developed a self‐assembled delivery system for doxorubicin. The system was sensitive to H 2 O 2 , GSH and pH, and delivered the drug to cytoplasm and nucleus of cancer cells after cell endocytosis.…”
Section: Ros‐activated Drug Delivery and Small‐molecular Prodrug Systemsmentioning
confidence: 99%
“…Images of doxorubicin and doxorubicin‐loaded delivery systems with or without GSH in HeLa cells to monitor drug release (right). Reproduced with permission . Copyright 2015, The Royal Society of Chemistry.…”
Section: Ros‐activated Drug Delivery and Small‐molecular Prodrug Systemsmentioning
confidence: 99%
“…ROS is an important indicator and a major characteristic of several pathological conditions, including cancer, where elevated intracellular levels have been reported in disease conditions . ROS‐responsive drug delivery carriers currently being developed mostly involve organochalcogens (selenium, tellurium, diselenium, and ditellurium), organoboron compounds (aryl boronic ester), sulfur containing compounds (thioether, thioketal, vinyl dithioether), aryl oxalates, and ferrocenes, either as cross‐linkers or as important constituents of polymeric backbone. Although very few studies have been reported for ROS‐responsive nanogels, it would be worthwhile to review some of the important reported results, due to the potential applicability of the ROS‐responsive units in the development of advanced redox‐responsive nanogel‐based systems in the near future.…”
Section: Emerging Areas In the Field Of Redox‐responsive Materialsmentioning
confidence: 99%